Biographical sketch of Dr. Celso Ramirez Bambarén - Bambarén Alatrista, Celso (2001)
The life and work of Dr. Celso Bambaren-Ramirez considered as one of the Peruvian wisemen of the XIX Century is presented. Bambaren was Senator of the Congress of the Republic, Vicerector of San Marcos and founder of the National Academy of Medicine. He was pupil and successor of Cayetano Heredia in the class of Descriptive Anatomy at San Fernando. In the scientific aspect he was predecessor of the knowledge about the movement of the heart auriculo-ventricular valves. In  the institutional aspect he was permanent defender of the university autonomy and chair freedom as well as fighter for cult freedom and rights equality between both men and women.